A new species of mossy frog (Anura: Rhacophoridae) from Northeastern Vietnam - Ninh, Hoa Thi; Nguyen, Tao Thien; Nguyen, Huy Quoc; Hoang, Ngoc Van; Siliyavong, Sonephet; Nguyen, Thinh Van; Le, Dzung Trung; Le, Quyet Khac; Ziegler, Thomas (European Journal of Taxonomy, 2022)
We describe a new species of Theloderma from northeastern Vietnam based on morphological differences and molecular divergence. Theloderma khoii sp. nov. is distinguishable from its congeners on the basis of a combination of the following characters: large size, SVL 52.1 mm in male, 59.4 mm in female; head length and width equal; vomerine teeth present; snout pointed and truncated, eye large, ED 4.7 mm in male, 5.6 mm in female, spinules on upper eyelid; tibiotarsal articulation reaches to the posterior border of the eye or the tip of the snout; dorsal skin very rough with large irregular gland ridges and warts, ventral surface of body granular; tips of all digits dilated but all considerably smaller than tympanum; dorsal surface mossy green or olive mottled with dark magenta. The distribution of the new species is unknown but probably extends into adjacent high elevation forested areas in Ha Giang Province, Vietnam and in Yunnan Province, China with an extent of occurrence of only < 1000 km2 and continuing decline in the quality of its habitat due to deforestation. Thus, we suggest the species should be considered Endangered following IUCN’s Red List categories.